2016
DOI: 10.1186/s12348-016-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial agreement between Goldmann visual field defects and fundus autofluorescence in patients with birdshot chorioretinopathy

Abstract: BackgroundThe purpose of this paper is to study the spatial agreement between visual field defects and ultra-wide field (UWF) fundus autofluorescence (FAF) in patients with birdshot chorioretinopathy (BSCR). The study is a retrospective, cross-sectional analysis of a university uveitis practice. Eight (8) eyes of five (5) patients with BSCR were included. Inclusion criteria were ability to fixate reliably. Goldmann visual fields (GVF) and UWF FAF were obtained, digitalized, and standardized. Analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Overall, these observations are consistent with smaller and mostly retrospective studies of FAF in eyes with BSCR. [2][3][4]38,39 Peripapillary hypoautofluorescence was strongly related with age and disease duration. Global hypoautofluorescence (i.e., present in both the macula and extramacular region) was associated longer disease duration (OR ¼ 1.46, P < 0.001) and presence of macular edema (OR ¼ 5.26, P < 0.001), suggesting that hypoautofluorescence may be a marker for chronicity and severity of BSCR.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Overall, these observations are consistent with smaller and mostly retrospective studies of FAF in eyes with BSCR. [2][3][4]38,39 Peripapillary hypoautofluorescence was strongly related with age and disease duration. Global hypoautofluorescence (i.e., present in both the macula and extramacular region) was associated longer disease duration (OR ¼ 1.46, P < 0.001) and presence of macular edema (OR ¼ 5.26, P < 0.001), suggesting that hypoautofluorescence may be a marker for chronicity and severity of BSCR.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between macular hypoautofluorescence and reduced BCVA is consistent with findings in eight individuals with BSCR reported by Koizumi et al 2 Piffer et al 38 studied 39 individuals with BSCR and also found that macular hypoautofluorescence was linked to worse visual acuity, but in contrast to our study, it was not affected by disease duration. The agreement between Goldmann visual field (GVF) and autofluorescence was analyzed in five individuals with BSCR by Jack et al 4 they found a relatively small overlap, suggesting that GVF is insensitive to anatomic RPE loss. Our data in a larger cohort found several relationships between FAF findings and visual field, using the automated Humphrey Field Analyzer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The following research is the use of ROI in fundus image processing to analyze various diseases. Many studies that define ROI based on processing needs by cropping [17][18][19][20][21][22][23][24]. Zahoor et al conducted a study of optical disc space ROI taking with Polar Transform method [25].…”
Section: Introductionmentioning
confidence: 99%